Market transparency and the marking precision of bond mutual fund managers - Gjergji Cici; Scott Gibson; Yalin Gündüz; John J. Merrick (University of Cologne, Centre for Financial Research (CFR), 2014)
The validity of the price marks placed on bonds for valuation purposes is important for a diverse group of stakeholders, including investors, mutual fund managers, dealers, pricing services, and financial regulators. We analyze the dispersion of monthend price marks simultaneously placed on identical corporate bonds by different US mutual fund managers before and after TRACE dissemination and introductions of issuers into Markit's Credit Default Swap spread database. We find large and statistically significant decreases in mark dispersion of newly disseminated bonds around key TRACE system rollout events. Dispersion for large, investment grade bonds fell 20% to 83% after the start of TRACE reporting. We also find evidence of spillover effects for non-disseminated bonds. During the pre-TRACE period, we find some evidence that mark dispersion fell for investment grade issuers after introductions into Markit's database. Our results provide support for the idea that the TRACE transparency initiative reduced information inequality within the institutional side of the market. The original NASD concern about people "operating largely in the dark" effectively applied to professional fund managers.
Keywords: 330; TRACE; CDS; bonds; transparency; marks